Construction of a Genetic Linkage Map Based on SNP Markers, QTL Mapping and Detection of Candidate Genes of Growth-Related Traits in Pacific Abalone Using Genotyping-by-Sequencing - Kho, Kang Hee; Sukhan, Zahid Parvez; Hossen, Shaharior; Cho, Yusin; Kim, Soo Cheol; Sharker, Md. Rajib; Jung, Hee-Jeong; Nou, Ill-Sup (Frontiers in Marine Science, 2021)
Pacific abalone (Haliotis discus hannai) is a commercially important high valued molluscan species. Its wild population has decreased in recent years. It is widely cultured in Korea. Traditional breeding programs have been implemented for hatchery production of abalone seeds. To obtain more genetic information for its molecular breeding program, a high-density linkage map and quantitative trait locus (QTL) for three growth-related traits was constructed for Pacific abalone. F1 cross population with two parents were sampled to construct the linkage map using genotyping by sequencing (GBS). A total of 664,630,534 clean reads and 56,686 SNPs were generated and 3,345 segregating SNPs were used to construct a consensus linkage map. The map spanned 1,747.023 cM with 18 linkage groups and an average interval of 0.55 cM. QTL analysis revealed two significant QTL in LG10 on the consensus linkage map of each growth-related trait. Both QTLs were located in the telomere region of the chromosome. Moreover, four potential candidate genes for growth-related traits were identified in the QTL region. Expression analysis revealed that these identified genes are involved in growth regulation of abalone. The newly constructed genetic linkage map, growth-related QTLs and potential candidate genes identified in the present study can be used as valuable genetic resources for marker-assisted selection (MAS) of Pacific abalone in molecular breeding program.